Amino acid response by Halofuginone in Cancer cells triggers autophagy through proteasome degradation of mTOR - Carlo Follo; Chiara Vidoni; Federica Morani; Alessandra Ferraresi; Christian Seca; Ciro Isidoro (Cell Communication and Signaling, 2019)
Abstract Background In the event of amino acid starvation, the cell activates two main protective pathways: Amino Acid starvation Response (AAR), to inhibit global translation, and autophagy, to recover the essential substrates from degradation of redundant self-components. Whether and how AAR and autophagy (ATG) are cross-regulated and at which point the two regulatory pathways intersect remain unknown. Here, we provide experimental evidence that the mammalian target of rapamycin (mTOR) complex 1 (mTORC1) specifically located at the lysosome level links the AAR with the autophagy pathway. Methods As an inducer of the AAR, we used halofuginone (HF), an alkaloid that binds to the prolyl-tRNA synthetase thus mimicking the unavailability of proline (PRO). Induction of AAR was determined assessing the phosphorylation of the eukaryotic translation initiation factor (eIF) 2α. Autophagy was monitored by assessing the processing and accumulation of microtubule-associated protein 1 light chain 3 isoform B (LC3B) and sequestosome-1 (p62/SQSTM1) levels. The activity of mTORC1 was monitored through assessment of the phosphorylation of mTOR, (rp)S6 and 4E-BP1. Global protein synthesis was determined by puromycin incorporation assay. mTORC1 presence on the membrane of the lysosomes was monitored by cell fractionation and mTOR expression was determined by immunoblotting. Results In three different types of human cancer cells (thyroid cancer WRO cells, ovarian cancer OAW-42 cells, and breast cancer MCF-7 cells), HF induced both the AAR and the autophagy pathways time-dependently. In WRO cells, which showed the strongest induction of autophagy and of AAR, global protein synthesis was little if any affected. Consistently, 4E-BP1 and (rp)S6 were phosphorylated. Concomitantly, mTOR expression and activation declined along with its detachment from the lysosomes and its degradation by the proteasome, and with the nuclear translocation of transcription factor EB (TFEB), a transcription factor of many ATG genes. The extra supplementation of proline rescued all these effects. Conclusions We demonstrate that the AAR and autophagy are mechanistically linked at the level of mTORC1, and that the lysosome is the central hub of the cross-talk between these two metabolic stress responses.